(untitled) (Al-Academy, 2024)
The research aims to evaluate the effectiveness of applying a graphic processing model based on the SCAMPER technique in enhancing the aesthetic quality of design units. A quasi-experimental method was employed, with a sample of 31 individuals producing 62 design units—31 before and 31 after applying the SCAMPER based graphic processing model. The aesthetic quality of these units was evaluated by experts, and the results revealed statistically significant differences between the aesthetic quality of the units produced before and after applying the model, with the latter showing superior results. The effectiveness of the model was further demonstrated by measuring the effect size using Cohen’s d, which indicated a substantial and significant impact on improving aesthetics of the design units. The research concluded by recommending further studies on other creative techniques that could be applied to graphic processing, aiming to enhance design outcomes and foster greater innovation in the field